Association of dental and prosthetic status with oral health-related auality of life in centenarians - Sekundo, Caroline; Langowski, Eva; Kilian, Samuel; Wolff, Diana; Zenthöfer, Andreas; Frese, Cornelia (International journal of environmental research and public health, 2021)
To date, there is little evidence on centenarians’ dental and prosthetic status or their oral-health-related quality of life (OHRQoL). Therefore, the aim of this study was to assess possible associations between sociodemographic and oral health factors, including prosthetic needs in this special age group and their potential influence on OHRQoL. Persons born before 1920 were recruited from population registries in south-western Germany. Fifty-five centenarians participated and underwent a comprehensive oral examination. Cognitive capacity was evaluated using the short Mini-Mental State Examination (S-MMSE, max. 21 points). At an S-MMSE > 10, an analysis of OHRQoL by means of the Geriatric Oral Health Assessment Index (max. ADD-GOHAI score 60 points) was performed (n = 43). Bivariate statistics and a linear regression model were used after variable selection to analyze data. Centenarians presented with a mean (SD) of 22 (7.2) missing teeth. Complete (65.5%) or partial dentures (21.8%) in at least one jaw were most common. One-third of the dentures needed repair/replacement; 16% of the centenarians presented with denture sores. In 60% of cases, OHRQoL was rated unsatisfactory (ADD-GOHAI < 57). Trouble biting or chewing resulted in the lowest levels of OHRQoL. Fewer remaining teeth, reduced functional capacity and removable prostheses correlated with an impaired OHRQoL (rs = −0.36, p = 0.01; rs = −0.34, p = 0.01; rs = −0.29, p = 0.03, respectively). After variable selection, the final linear regression model included only the number of missing teeth, the associated ADD-GOHAI score decreasing by 0.3 points per missing tooth. In conclusion, tooth loss and removable prostheses in need of repair or replacement are highly prevalent in centenarians. These factors seem to modulate OHRQoL negatively, assumedly due to impaired chewing function. Larger confirmatory studies are needed to validate these first results.
Gesehen am 31.01.2022